Real earnings management and firm value: Empirical evidence from Malaysia / Mohd Taufik Mohd Suffian, Zuraidah Mohd Sanusi and Nor'Azam Mastuki - Mohd Suffian, Mohd Taufik; Mohd Sanusi, Zuraidah; Mastuki, Nor'azam (Accounting Research Institute (ARI) & Faculty of Accountancy, 2015)
This research was conducted to study the connection between real earnings management (REM) activities and firm value. A sample of 6,216 suspected firms was collected from 2004 to 2011, We derived the relationship using the methods applied by Roychowdhury (2006). Using linear regression to determine the relationship of each REM activity of suspected firms with the firm value, we found a significant positive relationship between REM activities and firm value. When firms had more REM activities, the firm value increased. This outcome was caused by the existence of information asymmetry, which creates a friction between managers and shareholders, A significant relationship was also observed between leverage and firm value as well as between size and firm value. Thus, REM activities were concluded to increase firms' value.